Bacterial nanocellulose papers with high porosity for optimized permeance and rejection of nm-sized pollutants. (1st January 2021) - Mautner, Andreas; Bismarck, Alexander
Abstract: Access to clean potable water is increasingly becoming a struggle for whole humankind, thus water treatment to remediate wastewater and fresh water sources is an important task. Pollutants in the nanoscale, such as viruses and macromolecules, are usually removed by means of membrane filtration processes, predominantly nanofiltration or ultrafiltration. Cellulose nanopapers, prepared from renewable resources and manufactured by papermaking, have recently been demonstrated to be versatile alternatives to polymer membranes in this domain. Unfortunately, so far nanopaper filters suffer from limited permeance and thus efficiency. We here present nanopapers made from bacterial cellulose dispersed in water or different types of low surface tension organic liquids (alcohol, ketone, ether) through a simple papermaking process. Nanopapers prepared from organic liquids (BC-org) exhibited 40 times higher permeance, caused by a lower paper density hence increased porosity, compared to conventional nanopapers produced from aqueous dispersions, ultimately enhancing the efficiency of bacterial cellulose nanopaper membranes. Despite their higher porosity, BC-org nanopapers still have pore sizes of 15–20 nm similar to BC nanopapers made from aqueous dispersions, thus enabling removal of contaminants the size of viruses by a size-exclusion mechanism at high permeance.